(untitled) (Upper Saddle River, N.J., 2001)
For courses in Organizational Behavior, Individual Behavior in Organizations, and Industrial Psychology. This reader provides the best collection of classic, ground-breaking articles, as well as cutting-edge works in the field in a practical, reader-friendly format to support your experiential OB classroom.
Keywords: Psychology, Industrial,Organizational behavior,Hành vi tổ chức,Tâm lý học, công nghiệp